The mediating effect of TQM practice on cost leadership strategy and improvement of project management performance - Hosseini, S . S. (2014)
This study investigates the relationship between cost leadership strategy, total quality management (TQM) practices, and improvement of project management (IPM) performance. Based on a literature review, six main hypotheses and a theoretical model are developed on how these three domains are linked together. A data set collected from 128 mid to senior-level managerial employees of Malaysian engineering firms is utilized to validate the theoretical framework. The findings show that cost leadership strategy does not have a direct impact on IPM, consequently, it affects through the full mediation of TQM practices.